PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) 105 PADA BANK MUAMALAT KANTOR CABANG PEMBANTU PAREPARE - Sartika, Dewi; Damirah (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2023)
Abstract the purpose of this research is to find out what are the conditions for implementing Statement of Financial accounting Standards (PSAK) 105, the factors that influence the application of Statement of Financial accounting Standards (PSAK) 105, and how PSAK 105 is applied at Bank muamalat KCP Parepare. The research method used is a qualitative method using data namely data reduction, presentation, and conclusion. The results of this study indicate that : the condition of the mudharabah accounting treatment at Bank Muamalat Parepare sub branch office shows a good condition which can be seen in the financial summary report presented and the journalizing transactions that occur.